Nuevos registros de arañas (Arachnida: Araneae) para la Región del Cabo, península de Baja California, México - Jiménez, María Luisa; Palacios-Cardiel, Carlos; Maya-Morales, Julieta; Berrian, James Edwin (Instituto de Ecología, A.C., 2018)
We provide information of 11 new records of spiders of the Cape Region, Baja California peninsula. Two are new records for Mexico (Tennesseellum gollum and Araneus illaudatus); two genera (Edricus and Pozonia) and seven species are new records for Baja California Sur (Eustala emertoni, Arctosa minuta, Frontinella pyramitela, Chrysso albomaculata, Ariamnes mexicanus, Neospintharus baboquivari and Xysticus californicus). Philoponella arizonica is a reconfirmed species for this region. The peninsular discontinuous distributions and the peninsular-mainland discontinuous distributions of these species are discussed.